Improving Post-graduate Students Learning Activities through Lesson Study in Learning Forest-Prototype - Muhfahroyin Muhfahroyin; Anak Agung Oka (Biosaintifika: Journal of Biology & Biology Education, 2017)
Improving learning quality in 21st can not be separated from contextual learning and student-centered learning paradigm. The contextual lesson study program conducted in learning-forest prototype to build a learning community. The objectives of this research were to improve learning activities of postgraduate students in Biology Education department and to build a learning community. The implementation of lesson study was conducted in the Biology Learning Innovation subject for postgraduate students while practicing to observe open lesson in the undergraduate students which used learning forest-prototype. The postgraduate students took roles as planner, observer, and reflector in the plan, do (open lesson), and see (reflection) activities. The implementation was done in three cycles in even semester of academic year 2015/2016. Students learned collaboratively and contextually. The postgraduate students’ learning activities were observed by six observers from lecturer colleagues. The research results showed that the students were able to implement planning, open lesson, and reflection properly. The average of student’s learning activity grade was 91.11% from all of students, with the grade averages for planning, open lesson, and reflection activities were 88.89%, 93.33%, and 91.11% respectively. The implementation of this lesson study in the learning forest-prototype can be done in other relevant subjects to strengthen learning activities.